2015
DOI: 10.1177/1524838015585319
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Efficacy of the Child Advocacy Center Model

Abstract: The Child Advocacy Center (CAC) model has been presented as the solution to many of the problems inherent in responses by authorities to child sexual abuse. The lack of referral to therapeutic services and support, procedurally flawed and potentially traumatic investigation practices, and conflict between the different statutory agencies involved are all thought to contribute to low conviction rates for abuse and poor outcomes for children. The CAC model aims to address these problems through a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Working in multidisciplinary teams is said to cause less trauma for children and families, and leads to better decisions, more efficient use of resources, and less burnout (Ells 2000). This is the reasoning behind the establishment of Child and Youth Advocacy Centres (CYAC), which centralize all the necessary services for child victims (Herbert and Bromfield 2016;Jones et al 2007;McDonald, Scrum, and Rooney 2013). A recent review found evidence that multidisciplinary teams are more effective in improving mental health compared to standard practice (Herbert and Bromfield 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Working in multidisciplinary teams is said to cause less trauma for children and families, and leads to better decisions, more efficient use of resources, and less burnout (Ells 2000). This is the reasoning behind the establishment of Child and Youth Advocacy Centres (CYAC), which centralize all the necessary services for child victims (Herbert and Bromfield 2016;Jones et al 2007;McDonald, Scrum, and Rooney 2013). A recent review found evidence that multidisciplinary teams are more effective in improving mental health compared to standard practice (Herbert and Bromfield 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This systematic search of the literature builds on Herbert and Bromfield (2016), but going beyond CACs to include different types of multi-disciplinary approaches. This study was prompted by the discovery from the previous review that much CAC research focuses on improvements to criminal justice outcomes, with limited research evidence on child and family outcomes.…”
Section: What Are Multi-disciplinary Physical and Sexual Child Abuse mentioning
confidence: 99%
“…Multi-Disciplinary Teams (MDTs) typically have highly ambitious outcomes (Cross, 2001) including higher rates of successful prosecution of physical and sexual child abuse (Miller & Rubin, 2009), the reduction of additional trauma associated with inappropriate responses to abuse, and the reduction of child trauma symptoms (Conners-Burrow et al, 2012). However, even across some of the most developed models, there is a lack of a coherent theory of change about how these outcomes will be achieved (Herbert & Bromfield, 2016), with programs relying more on a set of principles that are assumed to contribute holistically to intended outcomes. This is further complicated by the fact that many of the intended outcomes of MDTs depend on a complex variety of other factors external to the program (e.g., conditions in the family, decisions made by police or prosecutors based on the likelihood of obtaining a prosecution).…”
mentioning
confidence: 99%
“…Literature suggests that a child's trauma can effectively be addressed through evidencebased therapies like trauma-focused cognitive behavioural therapy (TF-CBT) or parent-child interaction therapy, noting that it is imperative for referrals to be made as soon as possible (DeLorenzi et al, 2016;Vanderzee et al, 2016). Hubel et al (2014) found that the use of cognitive behavioural group therapy with abused children within CACs was associated with significant decreases in depression, loneliness, anxiety, and post-traumatic stressors (As cited in Herbert & Bromfield, 2015). Additionally, some studies have indicated that 80% of children who…”
Section: Victims and Mental Health Servicesmentioning
confidence: 99%
“…CACs are often used as a valued resource for families to receive referrals to mental health services during the child abuse investigation for both the direct victim as well as any nonoffending family members in need of services (Vanderzee et al, 2016). The CAC advocate is the primary professional responsible for referring children and families to mental health services (Herbert & Bromfield, 2015). Of concern however, a recent study by Vanderzee et al (2016) investigated the training needs of several American CACs in regard to mental health services for young victims and found that CAC advocates lacked training in child development and mental health for young traumatized children and that some CACs had indicated to partners that their centers were uncomfortable interviewing young child victims.…”
Section: Victims and Mental Health Servicesmentioning
confidence: 99%